2023
DOI: 10.1002/ange.202303500
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Enhancement of a Metal‐Organic Framework for Ultra‐Efficient Detection of Trace Benzene Vapor

Abstract: Indoor detection of volatile organic compounds (VOCs) concentration is necessary due to the serious toxicity hazards even at trace level. However, physisorbents usually exhibit weak interactions especially in the presence of trace concentrations of VOCs, thus exhibiting poor responsive signal. Herein, we report a new flexible metal-organic framework (MOF) that exhibits interesting pore-opening behavior after immersing in H 2 O. The pore-opening phase shows significant ( � 116 folds) and extremely fast (< 1 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Fluorescence sensing based on optical signal responses originating from sensor–analyte interactions has attracted considerable attention owing to its fast response, high sensitivity, and real-time detection . Fluorescent metal–organic frameworks (MOFs) are a type of hot sensor material owing to their structural and functional controllable design that can facilitate the molecular interaction between the analyte and MOF skeleton, thus resulting in a distinctively optical signal response. However, to the best of our knowledge, very few studies have reported on fluorescent MOFs for D 2 O detection. Humphrey et al examined the Eu­(III), Tb­(III), and Gd­(III) mix-coordinated isomorphic arylphosphine ligand-based PCM-22 for H 2 O detection in D 2 O .…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence sensing based on optical signal responses originating from sensor–analyte interactions has attracted considerable attention owing to its fast response, high sensitivity, and real-time detection . Fluorescent metal–organic frameworks (MOFs) are a type of hot sensor material owing to their structural and functional controllable design that can facilitate the molecular interaction between the analyte and MOF skeleton, thus resulting in a distinctively optical signal response. However, to the best of our knowledge, very few studies have reported on fluorescent MOFs for D 2 O detection. Humphrey et al examined the Eu­(III), Tb­(III), and Gd­(III) mix-coordinated isomorphic arylphosphine ligand-based PCM-22 for H 2 O detection in D 2 O .…”
Section: Introductionmentioning
confidence: 99%